Weight History and Subclinical Myocardial Damage. (4th January 2020) - Ndumele, Chiadi E; Cobb, Laura; Lazo, Mariana; Bello, Natalie A; Shah, Amil; Nambi, Vijay; Blumenthal, Roger S; Gerstenblith, Gary; Solomon, Scott D; Ballantyne, Christie M; Selvin, Elizabeth; Coresh, Josef
Abstract: BACKGROUND: Excess weight is associated with subclinical myocardial damage, as reflected by high-sensitivity cardiac troponin T (hs-cTnT) concentrations, which portends high heart failure risk. However, the association between weight history and myocardial damage is unknown. METHODS: We evaluated 9062 Atherosclerosis Risk in Communities (ARIC) visit 4 (1996–1999) participants with a body mass index (BMI) ≥ 18.5 kg/m 2 and no previous cardiovascular disease. We cross-tabulated visit 4 ("current") BMI categories of normal weight, overweight, and obese with those at visit 1 (1987–1989) and with BMI categories calculated from self-reported weight at age 25 years. Duration of obesity was calculated in years. A cumulative weight measure of "excess BMI-years" was also calculated [product of mean BMI (centered at 25 kg/m 2 ) over all ARIC time points × follow-up duration]. We used logistic regression to estimate associations of weight history metrics with increased hs-cTnT (≥14 ng/L) at visit 4. RESULTS: Overall, 623 individuals (7%) had increased hs-cTnT at visit 4. Within each current BMI category, previous excess weight was associated with increased hs-cTnT, with the strongest associations for those with past and current obesity [odds ratio (OR), 3.85; 95% CI, 2.51–5.90 for obesity at age 25 years and visit 4]. Each 10-year longer obesity duration was associated with increased hs-cTnT (OR, 1.26; 95% CI, 1.17–1.35). Each 100 higher excess BMI-years was also progressively associated with increased hs-cTnT (OR, 1.21; 95% CI, 1.14–1.27). CONCLUSIONS: Previous obesity and greater cumulative weight from young adulthood increase the likelihood of myocardial damage, indicating long-term toxic effects of adiposity on the myocardium and the need for weight maintenance strategies targeting the entire life span.